Analisis Kepatuhan Penggunaan Dana Desa yang Efektif dan Efisien di Desa Kemuning Muda Kecamatan Bunga Raya Kabupaten Siak Provinsi Riau - Rasiyem; Amrizal; Henny Mulyati; Dea Gusneli; Hardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Compliance with the use of village funds is the key to successful village development. This research aims to analyze the extent to which village fund management in Kemuning Muda has complied with applicable regulations and produced positive impacts for the village. The aim of this research is to determine the level of compliance with effective and efficient use of village funds. Implementing compliance in the use of village funds and the village government's commitment to the quality of the use of village funds is very important. The compliance methodology for effective and efficient use of village funds involves transparent planning, good understanding of regulations, strict supervision, and accountable financial management. The object of the research is the village of Kemuning Muda, Bunga Raya District, Siak Regency, Riau Province. Data is obtained and obtained from informants through interviews with respondents and created in an actual interview transcription scheme, making it easier to manage research data. It is hoped that this research can make a good contribution to the village government as the recipient and manager of village funds because all of this is intended for the Kemuning Muda community. The analytical method used is a qualitative descriptive method, in the form of interview results and respondent transcripts. The results of this research show that an analysis of compliance with the effective and efficient use of village funds in understanding regulations, financial management of village funds and anticipating potential misuse of financial management reports and the commitment of the village government and village consultative bodies have a very positive influence on the quality of village reports.